Early Bacterial Coinfections in Patients Admitted to the ICU With COVID-19 or Influenza: A Retrospective Cohort Study. (10th April 2023) - Bergmann, Felix; Gabler, Cornelia; Nussbaumer-Pröll, Alina; Wölfl-Duchek, Michael; Blaschke, Amelie; Radtke, Christine; Zeitlinger, Markus; Jorda, Anselm
Abstract : IMPORTANCE: Previous findings suggest that bacterial coinfections are less common in ICU patients with COVID-19 than with influenza, but evidence is limited. OBJECTIVES: This study aimed to compare the rate of early bacterial coinfections in ICU patients with COVID-19 or influenza. DESIGN, SETTING AND PARTICIPANTS: Retrospective propensity score matched cohort study. We included patients admitted to ICUs of a single academic center with COVID-19 or influenza (January 2015 to April 2022). MAIN OUTCOMES AND MEASURES: The primary outcome was early bacterial coinfection (i.e., positive blood or respiratory culture within 2 d of ICU admission) in the propensity score matched cohort. Key secondary outcomes included frequency of early microbiological testing, antibiotic use, and 30-day all-cause mortality. RESULTS: Out of 289 patients with COVID-19 and 39 patients with influenza, 117 ( n = 78 vs 39) were included in the matched analysis. In the matched cohort, the rate of early bacterial coinfections was similar between COVID-19 and influenza (18/78 [23%] vs 8/39 [21%]; odds ratio, 1.16; 95% CI, 0.42–3.45; p = 0.82). The frequency of early microbiological testing and antibiotic use was similar between the two groups. Within the overall COVID-19 group, early bacterial coinfections were associated with a statistically significant increase in 30-day all-cause mortality (21/68 [30.9%] vs 40/221 [18.1%]; hazard ratio, 1.84; 95% CI, 1.01–3.32). CONCLUSIONS AND RELEVANCE: Our data suggest similar rates of early bacterial coinfections in ICU patients with COVID-19 and influenza. In addition, early bacterial coinfections were significantly associated with an increased 30-day mortality in patients with COVID-19.